Measurement Accuracy Assessment For Laser Triangulation 3D Scanning Machine - Azlan, Khairul Azri; Omar, Mohammad Rafi; Hussin, Mohamed Saiful Firdaus; Abdullah, Muhammad Ilman Hakimi Chua; S. Chinniah, Eswaran (Blue Eyes Intelligence Engineering & Sciences Publication, 2020)
Laser triangulation 3D scanning machine is one of many types of 3D scanning technologies that are currently available in the current market. It is mainly use to capture object profiles as well as for measurement. Therefore, the measurement accuracy of laser triangulation 3D scanner was assessed and presented in paper. Three solid aluminum calibration block with known dimensions were fabricated by using CNC machine and these samples were named based on its profiles which are round, square and complex. Besides the laser triangulation 3D scanning machine, two more measuring equipment which are Vernier caliper and coordinate measuring machine were used as benchmarks. Three profiles were chose for each calibration block samples that made up of 9 profiles that have been measured and the deviation between the measuring values were analyzed. The results shown that the lowest deviation values for most of the profiles are from coordinate measuring machine and Vernier caliper measurement data. Nevertheless, the measurement deviation for laser triangulation 3D scanner are found to be comparable with other equipment.